A Review of Regulations and Standards for Long-Term Care Facilities: A Case Study of Thailand - Yanprapasiri, Chanisara; Jarutach, Trirat (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The ageing population is significantly elevating the demand for long-term care facilities for older people. Beyond health care services, the environment is important to improving the quality of life for elderly individuals. Long-term care facilities can be classified into various categories, including day care centers, assisted living, nursing homes, and hospices. Developed countries generally possess regulations and standards specific to various models, however Thailand has a singular, comprehensive regulation applicable to all facility types.The aim of this project aims to develop environmental standards specific to Thailand’s contexts. The study entailed the examination and comparison of regulatory structures and environmental standards from ten developed nations, concentrating on twenty-three government-issued documents. The results indicate that standard documents offer more detailed and comprehensive information than regulatory writings and can be classified into six main categories. Thai regulations mostly focus on basic safety and are deficient in several detailed elements seen in international standards that advocate for comprehensive well-being. The study advocates for the improvement of Thailand’s standards by augmenting current legislation to establish more comprehensive and interpretative rules. We expect that raising these criteria will markedly improve the quality of life for senior residents in long-term care institutions, providing them with conditions that promote privacy and dignity in their everyday existence.